2010
DOI: 10.1021/ac1012893
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Cardiac Cell Culture Model (μCCCM)

Abstract: Physiological heart development and cardiac function rely on the response of cardiac cells to mechanical stress during hemodynamic loading and unloading. These stresses, especially if sustained, can induce changes in cell structure, contractile function, and gene expression. Current cell culture techniques commonly fail to adequately replicate physical loading observed in the native heart. Therefore, there is a need for physiologically relevant in vitro models that recreate mechanical loading conditions seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 34 publications
0
79
0
Order By: Relevance
“…Recently, Giridharan et al reported that the fluid shear stress was significant ͑10 dynes/ cm 2 ͒ at the height of 200 m when the well was 250 m in depth. 47 However, the exposed shear stress, at the same height in the well of 2 mm in depth, was about 0, regardless of whether the fluid shear stress on the order was more than 10 dynes/ cm 2 or not. In this work, the positioned spherical embryo was attached on the bottom surface of culture chamber with a height approximately 500 m, whereas the well was as high as 1700 m. Additionally, the flow rate ͑24 mm/s͒ presented in the above mentioned model was much higher than that ͑4 l / min͒ used in our tests.…”
Section: B On-chip Embryonic Developmentmentioning
confidence: 89%
“…Recently, Giridharan et al reported that the fluid shear stress was significant ͑10 dynes/ cm 2 ͒ at the height of 200 m when the well was 250 m in depth. 47 However, the exposed shear stress, at the same height in the well of 2 mm in depth, was about 0, regardless of whether the fluid shear stress on the order was more than 10 dynes/ cm 2 or not. In this work, the positioned spherical embryo was attached on the bottom surface of culture chamber with a height approximately 500 m, whereas the well was as high as 1700 m. Additionally, the flow rate ͑24 mm/s͒ presented in the above mentioned model was much higher than that ͑4 l / min͒ used in our tests.…”
Section: B On-chip Embryonic Developmentmentioning
confidence: 89%
“…From there, the fl ow would travel in the blood, reaching the kidney, heart, bone marrow, brain, spleen, and vasculature. Reproduced with permission: lung, [ 26 ] Copyright 2011, Springer; gut, [ 40 ] Copyright 2012, The Royal Society of Chemistry; liver, [ 16 ] Copyright 2013, Elsevier; kidney, [ 50 ] Copyright 2013, The Royal Society of Chemistry; heart, [ 58 ] Copyright 2010, American Chemical Society; bone marrow, [ 67 ] Copyright 2014, Nature Publishing Group; brain, [ 69 ] Copyright 2012, Springer; spleen, [ 70 ] Copyright 2014, The Royal Society of Chemistry; and vasculature, [ 66 ] Copyright 2011, American Institute of Physics. Characterizing the toxicity of several compounds using liver co-culture and SMART-scale analysis HepG2/C3A and MDCK [20] Drug metabolism using liver and intestinal slices Harvested rat liver and intestinal slices [22] Testing the effects of ethanol-induced toxicity on liver slices Harvested rat liver slices [21] Functional analysis Creating model with bile canaliculi formation Harvested rat hepatocytes [14] Incorporated biosensors for pH monitoring in chip HepG2 [15] The kinetic reactions representing metabolism, measured and compared with mathematical model…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] Due to the advantages of 3D microfl uidic systems, there has been a shift towards using these designs to represent cardiac situations. [ 57 ] Giridharan et al [ 58 ] developed a model designed to replicate physical loading in the left ventricle. This microfl uidic cardiac cell culture model (µCCCM) contains a cell culture chamber, a pump, a collapsible pulsatile valve, and an adjustable hemostatic valve.…”
Section: Heartmentioning
confidence: 99%
“…Recently, Giridharan et al developed a microfluidic cardiac cell culture model (lCCCM) that incorporated pulsatile stretch and pressure on cardiac cells in a single device. 11 The mechanical stimulations can mimic various physiological conditions, including heart failure, hypertension, and hypotension. However, the structure and manipulation of this model device is too complicated for daily operations in a common biological laboratory.…”
Section: Introductionmentioning
confidence: 99%